(untitled) (Bioresearch Communications, 2022)
Ready-to-eat (RTE) meat products are food items that are extremely popular worldwide. Albeit documented with the alarming prevalence of pathogenic multidrug-resistant Listeria species in these food items worldwide, studies from the perspective of Bangladesh are absent. This study was devised with the aim to detect pathogenic Listeria monocytogenes in some of the most popular RTE meat products in Dhaka, Bangladesh. Thirty-nine such samples were investigated using biochemical tests and the Polymerase Chain Reaction (PCR) analysis. Following confirmatory tests and detection of Listeria species, the isolates were subjected to the Kirby-Bauer disc diffusion test to investigate their antibiotic-susceptibility patterns against some of the most commonly used antibiotics to treat listeriosis – the infection caused by Listeria. Five Listeria species were detected using biochemical and PCR tests. This constituted an overall prevalence rate of 12.8% (n = 39). Four out of the five Listeria species were concluded to be L. monocytogenes, while the remaining one was an L. innocua isolate. PCR analyses revealed all four of the L. monocytogenes isolates to have the virulence genes hlyA, plcB and actA, although no polymorphism was observed for these genes. Despite the presence of these pathogenic genes, antibiotic susceptibility tests showed promising results as some of the most commonly prescribed drugs against listeriosis were highly effective against the isolates. Even though the isolates showed little to no antibiotic resistance against the antibiotics used in the study, the presence of three virulence genes in all four L. monocytogenes isolates is still a cause for concern. Even more so, the prevalence of these pathogenic strains in a food item that is increasing in popularity in a country like Bangladesh, where awareness and surveillance against listeriosis is limited, can have dire consequences should an outbreak occurs. Bioresearch Commu. 9(1): 1160-1169, 2023 (January)